2018
DOI: 10.1073/pnas.1721443115
|View full text |Cite
|
Sign up to set email alerts
|

Scleral hypoxia is a target for myopia control

Abstract: Worldwide, myopia is the leading cause of visual impairment. It results from inappropriate extension of the ocular axis and concomitant declines in scleral strength and thickness caused by extracellular matrix (ECM) remodeling. However, the identities of the initiators and signaling pathways that induce scleral ECM remodeling in myopia are unknown. Here, we used single-cell RNA-sequencing to identify pathways activated in the sclera during myopia development. We found that the hypoxia-signaling, the eIF2-signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
251
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(258 citation statements)
references
References 59 publications
5
251
2
Order By: Relevance
“…Such remodeling of the sclera in myopia is associated with decreased amounts of collagen type 1 (the main component of its ECM), and treatment with atropine in several in vivo studies has been shown to increase the content of collagen-1 in sclera ECM. Another relevant correlate with myopia development is a thinning of the choroid and a decrease of blood perfusion of eye tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Such remodeling of the sclera in myopia is associated with decreased amounts of collagen type 1 (the main component of its ECM), and treatment with atropine in several in vivo studies has been shown to increase the content of collagen-1 in sclera ECM. Another relevant correlate with myopia development is a thinning of the choroid and a decrease of blood perfusion of eye tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 A study by Wu et al reported that scleral hypoxia plays a pivotal role in myopia induced scleral remodeling. 30 The triggers for scleral hypoxia are multifold. The retina contains the highest consumption of oxygen in the body and has continuous light exposure, which is highly susceptible to generating Reactive Oxygen Species (ROS).…”
Section: Molecular Concepts Underlying Myopia and Refractive Error Scmentioning
confidence: 99%
“…Wu et al postulated that hypoxia-induced myofibroblast trans-differentiation down-regulates type I collagen synthesis, which results in scleral structural changes, thus emphasizing the potential role of hypoxia in myopia. 30 Scleral architecture alterations with resultant staphyloma are detected using color fundus photography, ultrasonography, 2-dimensional Computed Tomography (CT) and Magnetic Resonance Imaging (MRI), and more recently a 3-dimensional MRI. The new high-resolution 3D MRI with volume rendering techniques analyzes the entire shape of the eye to delineate the posterior staphyloma in highly myopic eyes.…”
Section: Molecular Concepts Underlying Myopia and Refractive Error Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-hypoxic drugs such as salidroside and formononetin have shown antihypoxic effects to treat scleral hypoxia in myopia [53,54]. Scleral hypoxia, which is induced by Hypoxia-Inducible Factor-1α (HIF-1), triggers a signaling cascade for myofibroblast trans-differentiation leading to scleral extracellular collagenous matrix remodeling in progressing myopia [55]. Formononetin is known decrease HIF-1α, vascular endothelial growth factor (VEGF) and prolyl hydroxylase domain-2 (PHD-2), which are protective in hypoxia-induced retinal neovascularization [54].…”
Section: Anti-hypoxic Drugsmentioning
confidence: 99%